Concepções sobre ciência, tecnologia e sociedade e concepções de ensinar de futuros professores de ciências inseridos em um projeto baseado em arranjos produtivos locais - Santos, Maria Elane Mendonça (2017)
In this search, it was made a study about conceptions of Science, technology, and society (STS) and conceptions of teaching science of teachers of teaching field of science that took part of an institutional project, which deals with the theme of science and technology at fundamental school in Brazil. The respective search happened during a valid moment of the project, while 19 students experienced different moments of formal proposals. The first interference had as goal to collect conceptions about STS. For that, it was used the VOLTS questionnaire, an adaptation of Canavarro (2000). The second interference searched to see the conceptions of both teaching science and technology. At this case, it was thought an interview that had as ideal the seven deformations of Cachapuz et al. (2011). The third interference had as a goal to investigate the STS relations made by the students. This phase occurred almost in the middle of the institutional project. The search was accomplished from proposal of diagrams more suitable and less suitable related to STS. During fourth and last moments, it was seen again the conceptions of teaching science and technology. It was used the interview of the second moment adapted again, but with perspectives to provoke students’ conceptions. It was seen that along the process of searching, the moments experienced by students helped them to understand the factors seen as essential in training of science teachers, while a position before the role of experimentation of theory, the use of building of scientific knowledge of a context way and STS relations in day by day. It was noticed that during the investigation process, the moments lived by the students contributed, to a certain extent, to the understanding of certain factors seen as essential in the formation of the teacher of sciences, such as the posture before the role of experimentation and theory, The application of the construction of scientific knowledge in a contextual way and the CTS relations in daily life. The analysis of the four moments reveals the need for discussions about the nature of science in universities, since the distorted view on Science and Technology has an impact on CTS concepts and the very conception of teaching science because they can not understand which The role of science in this process. In this way, they focus the necessity of discussions guided in STS perspective in the science courses, to understand the importance, and the role of the teacher in conducting his/her students, training citizens capable to understand and change society to the better.